2019
DOI: 10.1080/03007995.2019.1699519
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of persistence and adherence between DPP-4 inhibitor administration frequencies in patients with type 2 diabetes mellitus in Japan: a claims-based cohort study

Abstract: Objective: To explore persistence and adherence with once-daily, twice-daily, or once-weekly DPP-4 inhibitors (DPP-4i) in Japanese patients with type 2 diabetes. Methods: This retrospective, longitudinal, observational cohort study used data from the Japanese nationwide hospital-based Medical Data Vision (MDV) administrative claims database. Data were collected for patients given a new DPP-4i prescription between May 2015 and June 2017 with 1-year follow-up until May 2018. Treatment persistence was defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In clinical practice, where quick, efficient and low‐cost approaches to evaluate adherence is desired, this could help the physicians to rely confidently on either one week or one month self‐reported adherence in making prescribing decisions while having to ask lesser number of questions. Although several studies have reported how daily, weekly and monthly drug regimens could help in determining the adherence rate, 18,19 we could not find much‐published literature on similar correlations for adherence based on different time‐periods. A study on 78 patients receiving antiretroviral treatment showed that reported adherence is more accurate for longer recall periods as compared with one, two and three days 22 .…”
Section: Discussionmentioning
confidence: 81%
“…In clinical practice, where quick, efficient and low‐cost approaches to evaluate adherence is desired, this could help the physicians to rely confidently on either one week or one month self‐reported adherence in making prescribing decisions while having to ask lesser number of questions. Although several studies have reported how daily, weekly and monthly drug regimens could help in determining the adherence rate, 18,19 we could not find much‐published literature on similar correlations for adherence based on different time‐periods. A study on 78 patients receiving antiretroviral treatment showed that reported adherence is more accurate for longer recall periods as compared with one, two and three days 22 .…”
Section: Discussionmentioning
confidence: 81%
“…The persistence of once-daily (QD) DPP4 inhibitors was comparable to that of twice-daily (BID) DPP4 inhibitors (HR [95% CI] of discontinuation for BID regimen: 1.022 [0.994–1.050], p = 0.1187) [ 59 ]. Similarly, the difference between the adherence rates of BID regimen and QD regimen was not significant (OR [95% CI] of adherence for BID regimen: 0.945 [0.780–1.145], p = 0.5636) [ 59 ].…”
Section: Dipeptidyl Peptidase-4 Inhibitorsmentioning
confidence: 99%
“…The persistence of once-daily (QD) DPP4 inhibitors was comparable to that of twice-daily (BID) DPP4 inhibitors (HR [95% CI] of discontinuation for BID regimen: 1.022 [0.994–1.050], p = 0.1187) [ 59 ]. Similarly, the difference between the adherence rates of BID regimen and QD regimen was not significant (OR [95% CI] of adherence for BID regimen: 0.945 [0.780–1.145], p = 0.5636) [ 59 ]. On the other hand, QD regimen showed significantly higher adherence and persistence rates than once-weekly (QW) regimen (HR [95% CI] of discontinuation for QW regimens: 1.699 [1.585–1.822], p < 0.0001; OR [95% CI] of adherence for QW regimen: 0.029 [0.024–0.036], p < 0.0001) [ 59 ].…”
Section: Dipeptidyl Peptidase-4 Inhibitorsmentioning
confidence: 99%
“…HAE management should be periodically reviewed and discussed with the patient [ 3 ]. Although findings of studies involving other diseases differ on the optimal route and frequency of administration for maximal treatment adherence [ 28 – 30 ], a qualitative review of 102 articles demonstrated that convenience of administration is likely to have a favorable effect on adherence [ 31 ].…”
Section: Discussionmentioning
confidence: 99%